2018
DOI: 10.26871/oactiva.v1i2.133
|View full text |Cite
|
Sign up to set email alerts
|

Prevalencia De Maloclusiones Dentales en Escolares De 12años en Monay - Cuenca 2016

Abstract: OBJETIVO: El presente estudio tuvo como objetivo determinar la prevalencia de maloclusiones dentales en niños de 12 años en etapa escolar de la parroquia Monay en la ciudad de Cuenca-Ecuador. MATERIALES Y MÉTODOS: Este estudio epidemiológico fue de tipo descriptivo, observacional y corte transversal, la evaluación clínica bucal se realizó con la participación de 252 escolares, de los cuales 124 (49%) representaron al sexo femenino y 128 (51%) representaron al sexo masculino, presentando así una muestra equitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In relation to the prevalence of malocclusions according to the type of school management, the study conducted by Fajardo et al (2016) in a population of 252 schoolchildren, reported a greater number of affected schoolchildren for fiscal schools.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In relation to the prevalence of malocclusions according to the type of school management, the study conducted by Fajardo et al (2016) in a population of 252 schoolchildren, reported a greater number of affected schoolchildren for fiscal schools.…”
Section: Discussionmentioning
confidence: 99%
“…Latin America is not the exception, according to the Pan American Health Organization (PAHO), as the prevalence of this pathology exceeds 80%. As a result, the WHO states that malocclusions take the third place among pathologies that affect oral health (Ramirez et al, 2012;Fajardo & González, 2016;Fundagul et al, 2015).…”
mentioning
confidence: 99%
“…These conditions cause functional, emotional and social conditions in the individual. 18 If crowding is related to poor dental position, it can be treated with dental movements, which can take multiple phases. Generally, in orthopedic phase, which consists of expansion if patient's conditions warrant it and they are a candidate; with maxillary expansion and an orthodontic phase through alignment, leveling and detailing with brackets (Figure 3).…”
Section: Clinical Manifestationmentioning
confidence: 99%

Dental crowding: a review

Rosas López Portillo,
Gámez Valenzuela,
Rosas Alcaraz
et al. 2024
Int J Res Med Sci